2012
DOI: 10.1016/j.eats.2012.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Bursectomy and Iliotibial Tract Release as a Treatment for Refractory Greater Trochanteric Pain Syndrome: A New Endoscopic Approach With Early Results

Abstract: Abstract:Greater trochanteric pain syndrome (GTPS) is associated with excessive tension between the iliotibial band (ITB) and the greater trochanter. Several endoscopic procedures have been reported, but in most cases the endoscopic approach only consists of a bursectomy. The ITB and fascia lata act as a lateral tension band to resist tensile strains on the concave aspect of the femur and are often implicated as the source of GTPS. We therefore believe that the ITB must be addressed. We describe an endoscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 9 publications
0
17
0
1
Order By: Relevance
“…This surgery is performed either as an open or an arthroscopic procedure, and the technique of ITB release varies from proximal Z-plasty to proximal longitudinal release, T-section and distal Z-plasty [73,[87][88][89][90][91]. There are no data on the comparative efficacy of these procedures, and all studies (case series) have reported good to excellent shortto medium-term outcomes.…”
Section: Surgical Interventionsmentioning
confidence: 96%
“…This surgery is performed either as an open or an arthroscopic procedure, and the technique of ITB release varies from proximal Z-plasty to proximal longitudinal release, T-section and distal Z-plasty [73,[87][88][89][90][91]. There are no data on the comparative efficacy of these procedures, and all studies (case series) have reported good to excellent shortto medium-term outcomes.…”
Section: Surgical Interventionsmentioning
confidence: 96%
“…This in turn causes local inflammation, degeneration of the tendons and increased tension of the ITB. 23 Approximately two thirds of individuals with GTPS have coexisting hip joint osteoarthritis or low back pain. 24 Having a higher than normal body mass index is also a likely contributing factor to GTPS.…”
mentioning
confidence: 99%
“…12,13,27 The techniques of ITB lengthening varied between the studies, and all were proximal ITB techniques except one, which was distal. 13 Z-lengthening was undertaken in two studies 27,65 ; cross-incision was used in one study 23 and longitudinal release in one study. 68 Trochanteric bursectomy was performed in all the proximal procedures.…”
mentioning
confidence: 99%
“…Baker et al, in a prospective study of 25 patients who underwent arthroscopic bursectomy and were assessed at a mean follow-up of 26 months, showed significant improvement in Visual Analog Score (VAS; 7.2-3.1), Harris Hip Scores (HHS; 51-77), and short-form 36 scores from the preoperative status scores [22]. Variations on the endoscopic bursectomy have been described, including an ITB release either preceding [23] or subsequent to the bursectomy [25], with favorable results. Similarly, successful treatment of GTB secondary to gluteus medius and minimus calcific tendonitis has been described by Kandemir et al [26].…”
Section: Greater Trochanteric Bursitismentioning
confidence: 99%